التقصي عن الإصابة بالطفيليات الخارجية عند النوعين السمكيين القجاج Sparus aurata والغبس Boops boops في المياه البحرية السورية - حسن, محمد; لايقة, تغريدة; فاضل, منار (Latakia University Journal -Biological Sciences Series, 2018)
This study aimed to investigate the exoparasites in Sparus aurata and Boops boops in the Syrian marine waters. A total of 55 individuals of Sparus aurat and 85 of Boops boops were collected from different localities (RasAlBaseet, RasIbenHani, Lattakia) during the period from 16/10/2015 to 15/09/2016 using trawls. The skin, mouth cavity, nostrils and gills of all individuals were examined. We isolated in this study one exoparasit species Furnistinia echeneis that belongs to the (Family: Diplectanidae) from Saprus aurata gills, with prevalence of 32.72% and intensity of 1.6. We also isolated Axine belones that belongs to the(Family: Axinidae) from Boops boops gills with prevalence of 56.47% and intensity of 2.5. Our results recorded the highest infection by both isolated exoparasite species in both fish species in spring. Indeed, these two species were isolated for the first time in the Syrian marine waters. هدف البحث الحالي إلى التقصي عن الإصابة بالطفيليات الخارجية عند النوعين السمكيين القجاجSparus aurata , والغبس Boops boops في المياه البحرية السورية. جمعت العينات السمكية من مناطق صيد مختلفة (رأس البسيط ورأس ابن هاني واللاذقية) خلال الفترة الممتدة بين 2015 /10 /16 و2016 / 9 /15, باستخدام الصنانير والشباك المبطنة. وبلغ العدد الإجمالي للأفراد المصطادة 55 فرداً من القجاج و85 فرداً من الغبس, وفحص الجلد والتجويف الفموي والفتحتين الأنفيتين والتجويف الغلصمي والغلاصم لجميع الأفراد المصطادة. عزل في هذا البحث النوع الطفيلي Furnistinia echeneis التابع لفصيلة Diplectanidae من غلاصم سمك القجاج بنسبة إصابة (32.72)% وشدة إصابة (1.6) طفيلي/سمكة, كما عزل النوع الطفيلي Axine belones التابع لفصيلة Axinidae من غلاصم سمك الغبس بنسبة وشدة إصابة (56.47)%, (2.5) على التوالي. وقد أظهرت النتائج أعلى نسبة وشدة إصابة بالنوعين الطفيليين عند النوعين السمكيين المدروسين في فصل الربيع. وهذه هي المرة الأولى التي يعزل فيها هذان النوعان الطفيليان من النوعين السمكيين المدروسين في المياه البحرية السورية.